2020
DOI: 10.1037/ocp0000177
|View full text |Cite
|
Sign up to set email alerts
|

The long reach of the leader: Can empowering leadership at work result in enriched home lives?

Abstract: Work-home enrichment occurs when employees' work roles and experiences lead to benefits and resources that improve the quality of life in the home role. Guided by self-determination theory (SDT), we developed a serial mediation model in which empowering leadership predicted workhome enrichment via satisfaction of innate psychological needs of SDT and then via work engagement. Four-waves of data over a 9-month period were obtained from 289 full-time U.S. employees. Structural equation modeling and the PROCESS m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 55 publications
(88 reference statements)
2
16
0
Order By: Relevance
“…Indeed, the results of other spillover studies have shown standardized effect sizes of a comparable magnitude (e.g. Kim & Beehr, 2020;Siu et al, 2015;Siu et al, 2010). Rastogi and Chaudhary (2018) examined the relationship between job crafting and work-family enrichment through work engagement in a cross-sectional design and found standardized effect sizes between .10 and .20, which were larger than the effect sizes for the indirect effects in our study.…”
Section: Limitations and Future Researchsupporting
confidence: 50%
See 1 more Smart Citation
“…Indeed, the results of other spillover studies have shown standardized effect sizes of a comparable magnitude (e.g. Kim & Beehr, 2020;Siu et al, 2015;Siu et al, 2010). Rastogi and Chaudhary (2018) examined the relationship between job crafting and work-family enrichment through work engagement in a cross-sectional design and found standardized effect sizes between .10 and .20, which were larger than the effect sizes for the indirect effects in our study.…”
Section: Limitations and Future Researchsupporting
confidence: 50%
“…Researchers have indeed demonstrated that the positive state of work engagement can persist after the workday and promote functioning in other domains, contributing to work-life enrichment (e.g. Kim & Beehr, 2020;Rastogi & Chaudhary, 2018;Straub et al, 2019). Work engagement has also been linked to more specific outcomes, such as employees' willingness to invest in their relationships with their life partners in the home domain (Bakker et al, 2012) as well as life satisfaction and community involvement (Eldor et al, 2020).…”
Section: Toward a Work-sports Spillover Process: Work Engagement As Amentioning
confidence: 99%
“…This logic is supported by studies suggesting that empowering leadership reduces the influence of specific (techno)stressors on employee outcomes. For example, Windeler et al ( 2017 ) reported that empowering leaders reduce the influence of techno-complexity, while Kim and Beehr ( 2020 ) observed such leaders to mitigate negative technological spillovers from work to home. Additional empirical support underpins that leaders that build employees' resource base (Harris et al, 2015 ) and stimulate their participative decision making (Turel and Gaudioso, 2018 ) significantly reduce the influence of technostress(ors) on employee outcomes, like emotional exhaustion and job performance.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, an increasingly important aspect of leadership encompasses bosses' empowering leadership behaviors towards their subordinates [56,57]. Some studies suggest that empowerment, in its different manifestations, can affect employees' health and well-being [58][59][60][61].…”
Section: Empowerment Health and Well-beingmentioning
confidence: 99%